1990
DOI: 10.1111/j.1469-7998.1990.tb04316.x
|View full text |Cite
|
Sign up to set email alerts
|

Living fast and dying young: A comparative analysis of life‐history variation among mammals

Abstract: Recent comparative studies point to the importance of mortality schedules as determinants in the evolution of life‐history characteristics. In this paper, we compare patterns of mortality from natural populations of mammals with a variety of life histories. We find that, after removing the effects of body weight, mortality is the best predictor of variation in life‐history traits. Mammals with high levels of natural mortality tend to mature early and give birth to small offspring in large litters after a short… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
793
2
8

Year Published

1994
1994
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,034 publications
(848 citation statements)
references
References 84 publications
25
793
2
8
Order By: Relevance
“…Recently, Hochberg et al (1992) investigated in detail with the aid of a mathematical model just how parasites could affect the most fundamental of their host's life-history traits, the time to first reproduction (Promislow and Harvey, 1990). They showed that hosts subjected to virulent parasites and unable to resist by other means [e.g.…”
Section: Nous Proposons Une Revue Des éTudes Portant Sur Les Effets Dmentioning
confidence: 99%
“…Recently, Hochberg et al (1992) investigated in detail with the aid of a mathematical model just how parasites could affect the most fundamental of their host's life-history traits, the time to first reproduction (Promislow and Harvey, 1990). They showed that hosts subjected to virulent parasites and unable to resist by other means [e.g.…”
Section: Nous Proposons Une Revue Des éTudes Portant Sur Les Effets Dmentioning
confidence: 99%
“…More generally, harsh, violent conditions are valid cues (not necessarily processed consciously) that it is in one's reproductive interests to allocate energetic and somatic resources to reproductive maturity and mating effort in the short-term, rather than to investments that will redound to fitness only over a longer time horizon [16]. Here, we explored whether this 'live fast, die young' principle [17] explains individual differences in cooperation with a highly cooperative partner and retaliatory defection in an Iterated Prisoner's Dilemma (IPD; figure 1). …”
Section: Introductionmentioning
confidence: 99%
“…We predict that, after controlling for body mass: (i) volant species will live longer than non-volant species, because they can more easily evade predators and unfavourable conditions [11 -13]; (ii) nocturnal, crepuscular or cathemeral species will live longer than diurnal species, because species that are active at night or dusk are likely to be harder for predators to detect [12,19]; (iii) species which forage in non-terrestrial environments (i.e. species which feed in trees, water or aerially) will live longer than terrestrial foragers, because they will be more capable of escaping from predators than species that feed on the ground [13,17,20]; and (iv) fossorial (i.e.…”
Section: Introductionmentioning
confidence: 99%